2017
DOI: 10.4238/gmr16019369
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in codons 12 and 13 of K-ras exon 2 in colorectal tumors of Saudi Arabian patients: frequency, clincopathological associations, and clinical outcomes

Abstract: ABSTRACT. Mutations in codons 12/13 of K-ras exon 2 are associated with reduced benefit from anti-epidermal growth factor receptor antibody treatment for metastatic colorectal cancer (CRC). Here, we evaluated the frequency of K-ras mutations and their relationship with clinicopathological features and treatment outcomes in Saudi Arabian patients with CRC. The genetic status of K-ras was determined in 300 patients diagnosed with CRC. Clinical information was collected retrospectively. K-ras was wild-type in 58%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The frequency of KRAS mutations in our study group did not differ when compared with those of most other studies in Europe and the United States (23,24). Previous studies that enrolled a relatively large number of Arabian patients with different stages of the disease, reported KRAS mutation rates of 28-56% in Saudi Arabia (19,(25)(26)(27), 23-32% in Tunisia (22,28,29), 33-44% in Jordan (30,31) and 42% in Egypt (32).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of KRAS mutations in our study group did not differ when compared with those of most other studies in Europe and the United States (23,24). Previous studies that enrolled a relatively large number of Arabian patients with different stages of the disease, reported KRAS mutation rates of 28-56% in Saudi Arabia (19,(25)(26)(27), 23-32% in Tunisia (22,28,29), 33-44% in Jordan (30,31) and 42% in Egypt (32).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found no significant association between the overall frequency of K-ras mutations and patients’ characteristics and/or clinicopathological features. In literature, conflicting results were documented regarding the association between K-ras mutations and patients’ characteristics and/or clinicopathological features [ 17 - 21 ]. For example, while some studies showed that females are significantly more likely to have mutant K-ras than males [ 18 , 22 ], other studies showed the opposite (i.e males are significantly more likely to have mutant K-ras than females) [ 17 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequently happens in exon 2 (codons 12 and 13), changing the guanine/adenine that during the formation of protein replaces the amino acid. Exon mutations may occur less often 3 (codons 61) and exon 4 (codons 146) (23).…”
Section: Methodsmentioning
confidence: 99%
“…Since 2009, the American Society of Clinical Oncology has recommended that mAb treatment candidates be screened for K-ras mutations in codons 12 and 13. (23), because mutations in this gene identify patients who do not respond well to therapy with anti-EGFR drugs (24).…”
Section: Introductionmentioning
confidence: 99%